Novel POLG1 mutations associated with neuromuscular and liver phenotypes in adults and children. Issue 3 (27th February 2009) - Stewart, J D; Tennant, S; Powell, H; Pyle, A; Blakely, E L; He, L; Hudson, G; Roberts, M; du Plessis, D; Gow, D; Mewasingh, L D; Hanna, M G; et al.
Abstract : Background: The POLG1 gene encodes the catalytic subunit of DNA polymerase gamma, essential for mitochondrial DNA replication and repair. Mutations in POLG1 have been linked to a spectrum of clinical phenotypes, and may account for up to 25% of all adult presentations of mitochondrial disease. Methods and results: We present 14 patients, with characteristic features of mitochondrial disease including progressive external ophthalmoplegia (PEO) and Alpers–Huttenlocher syndrome and laboratory findings indicative of mitochondrial dysfunction, including cytochrome c oxidase (COX) deficiency and multiple deletions or depletion of the mitochondrial DNA. Four novel POLG1 missense substitutions (p.R597W, p.L605R, p.G746S, p.A862T), are described, together with the first adult patient with a recently described polymerase domain mutation (p.R1047W). All novel changes were rare in a control population and affected highly conserved amino acids. Conclusion: The addition of these substitutions—including the first report of a dinucleotide mutation (c.1814_1815TT>GC)—to the growing list of defects further confirms the importance of POLG1 mutations as the underlying abnormality in a range of neurological presentations.